Treatment of Primary Hepatocellular Carcinoma (HCC) with Active Pencil Beam Scanning Protons in Singapore - Yoo, Seunghoon (Radioterapi & Onkologi Indonesia, 2024)
We report a patient with HCC treated with protons for the first time in Singapore. The prescription was 66 Gy in 10 fractions. Treatment plans and proton beam delivery was performed using an active pencil beam scanning mode using the Probeam system (Varian Medical, Palo Alto, CA). Two treatment plans, one is deep inspiration breath holding (DIBH) and the other is free breathing (FB) plan, were prepared following observation of liver motion during 4DCT image acquisition. For the actual treatment, the free breathing mode plan was selected since the DIBH mode was not advisable following evaluation of patient setup image prior to the first treatment.